Exploring views and experiences of the general public’s adoption of digital technologies for healthy lifestyle in Singapore: a qualitative study - Roystonn, Kumarasan; AshaRani, P. V.; Devi, Fiona; Wang, Peizhi; Zhang, Yunjue; Jeyagurunathan, Anitha; Abdin, Edimansyah; Car, Lorainne Tudor; Chong, Siow Ann; Subramaniam, Mythily (Frontiers in Public Health, 2023)
• A key strength is the broad and diverse demographic interviewed, including men and women across age, ethnic, education and socioeconomic categories. • Our sample comprised those who had agreed to be contacted for the qualitative study as such this particular group may have been more willing to share their perceptions and experiences.• This was a single interview and in the midst of the pandemic, and so it is not clear whether experiences would differ in the longer term. • Our sample comprised community-dwelling residents who lived in Singapore, spoke either English, Chinese, Malay or Tamil, and thus our findings may not be transferable to those in other settings and countries.Chronic preventable diseases are now responsible for more than half of the deaths in high income countries. Encouraging healthy lifestyle behaviors should be the overarching priority for the response to this health crisis especially when individuals are expected to take greater responsibility for managing their health and well-being today. Yet, there is suboptimal adherence to active healthy lifestyle behaviors in the general population. Digital technologies are able to better promote and sustain positive lifestyle habits. From a public health perspective, one of the most powerful levers for influencing population health lie today in digital technological innovations that make healthy living convenient and an accessible choice. Little is known about the general adult population's adoption of digital technology to support healthy lifestyle in Singapore. Drawing on the technological acceptance model, the current study intended to gain an in-depth qualitative understanding of the determinants of digital technology adoption for healthy lifestyle among community-dwelling adults in Singapore. We propose that this theory could explain in part the phenomenon of interest, and further make the case for a local conceptual model to examine technological adoption for healthy lifestyle in Singapore.